2021
DOI: 10.21873/invivo.12555
|View full text |Cite
|
Sign up to set email alerts
|

Liver Metastatic Colorectal Tumor Cells Change Their Phenotype During Consecutive Passages on Chick Embryo Chorioallantoic Membrane: Lessons from the Lab to the Clinic

Abstract: Background/Aim: Colon cancer liver metastases with desmoplastic growth pattern (dGP) have a highly heterogeneous therapy response. The aim of the study was to evaluate the dGP liver metastasis molecular profile from a chemo-naive patient by mimicking metastatic process on an experimental chick embryo chorioallantoic membrane (CAM) model. Materials and Methods: Three successive CAM passages of dGP human colorectal liver metastases were immunophenotyped for keratin (K) 8, and 20, CLIC1, VEGF, EGFR, CD34, podopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…On the other hand, a study performed using an experimental model on the chick chorioallantoic membrane of an embryonated egg indicated metastasis with a d-HGP, cord-like structures formed by CD34+/Ki67+ cells, vessels with a wide lumen and proliferative endothelium, and vessels with large dimensions. Intraluminal pillars and the intussusception mechanism were found [20]. In the present study, sprouting and intussusception mechanisms were identified mainly in LMs with a d-HGP and p-HGP.…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, a study performed using an experimental model on the chick chorioallantoic membrane of an embryonated egg indicated metastasis with a d-HGP, cord-like structures formed by CD34+/Ki67+ cells, vessels with a wide lumen and proliferative endothelium, and vessels with large dimensions. Intraluminal pillars and the intussusception mechanism were found [20]. In the present study, sprouting and intussusception mechanisms were identified mainly in LMs with a d-HGP and p-HGP.…”
Section: Discussionsupporting
confidence: 53%
“…Circulating cancer stem cells were engrafted to analyze aggressiveness and proliferation capacity of primary tumors, closely resembling its complex structure for pre-clinical drug screenings and biomarker discovery ( 129 ). Re-grafting and repetitive passaging of human colorectal liver metastases on the CAM, paralleled by immunophenotyping and evaluation of invasiveness, enabled long-term monitoring of PDX tumors, displaying an interesting approach to study tumor progression in ovo ( 130 ) ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last 3 years, publications using the CAM assay for tumor induction from patient biopsies have increased significantly (Figure 2A). Of the 14 articles included in the systematic review about this method [1,71,[76][77][78][79][80][81][82][83][84][85][86][87], 29% used a biopsy from colorectal cancer, followed by ovarian cancer (12%) and breast cancer (11%) (Figure 8A). Regarding The effectiveness of the trial has been demonstrated through the analysis of metastases, with the organs with the most prevalence in the formation of metastases being the liver (43%), followed by the distal CAM in 29% of the studies and the lungs and brain (14% each) (Figure 7D).…”
Section: Efficacy Of the Patient-derived Xenograft Model And Its Use ...mentioning
confidence: 99%
“…In the last 3 years, publications using the CAM assay for tumor induction from patient biopsies have increased significantly (Figure 2A). Of the 14 articles included in the systematic review about this method [1,71,[76][77][78][79][80][81][82][83][84][85][86][87], 29% used a biopsy from colorectal cancer, followed by ovarian cancer (12%) and breast cancer (11%) (Figure 8A). Regarding methodologies, only two articles followed ex ovo methodology [71,83], while the rest of the articles used in ovo assays (Figure 8B).…”
Section: Efficacy Of the Patient-derived Xenograft Model And Its Use ...mentioning
confidence: 99%